The Value of Clinical Teachers for EMR Implementations and Conversions - Stevens, L.A.; Pantaleoni, J.L.; Longhurst, C.A. (Applied Clinical Informatics, 2015)
Effective physician training is an essential aspect of EMR implementation. However, it can be challenging to find instructors who can present the material in a clinically relevant manner. The authors describe a unique physician-training program, utilizing medical students as course instructors. This approach resulted in high learner satisfaction rates and provided significant cost-savings compared to alternative options.Citation: Stevens LA, Pantaleoni JL, Longhurst CA. The value of clinical teachers for EMR implementations and conversions. Appl Clin Inf 2015; 6: 75–79http://dx.doi.org/10.4338/ACI-2014-09-IE-0075
Keywords: Physicians; electronic medical record; EMR; education